دور المحافظة على الأراضي الزراعية الباكستانية في تحقيق التنمية المستدامة: دراسة استقرائية تمثيلية في ضوء الاقتصاد الإسلامي: The Impact of Conservation of Pakistani Agricultural Lands on Achieving Sustainable Development: An Exploratory Representational Study in the Light of Islamic Economics - Dr. Israr Khan; Dr. Umme Habiba (International Research Journal of Arabic and Islamic Studies, 2024)
Pakistan is one of the leading agricultural countries, where its agricultural lands are considered among the most important natural and economic resources. However, despite this, it has faced numerous challenges affecting agricultural production, resulting in a shortage of various agricultural products. Consequently, Pakistan has been compelled to import most agricultural and food products from other countries, despite being an agrarian nation. These challenges stem from the misuse and neglect of agricultural lands. Therefore, there is a need to revert to the correct path in utilizing agricultural lands to achieve sustainable development. This study aims to explore the role of preserving agricultural lands in achieving sustainable development in the light of Islamic economics. Islamic economics emerges as an inspiring model that offers guidance and directives for conserving and developing agricultural lands in ways that balance the needs of the current generation with those of future generations. By studying the principles of conserving agricultural lands advocated by Islamic economics, these concepts can be applied to the Pakistani agricultural context, leading to increased agricultural productivity and the realization of sustainable development.